Clinicopathological Analysis of Rhabdomyosarcoma Patients Undergone Radiotherapy in Two Referral Hospitals in West Java - Muhammad Syah Misuari Sabirin; Hermin Aminah Usman; Anglita Yantisetiasti; Mas Adi Sunardi (Eduvest - Journal of Universal Studies, 2024)
Rhabdomyosarcoma (RMS) is a type of malignant soft tissue neoplasm that develops from mesenchymal cells of skeletal muscle origin. This condition comprises multiple subtypes with distinct histologic characteristics. While cases of RMS are uncommon overall, they are more frequently diagnosed in children, although adults can also be affected. Treatment options for RMS include radiotherapy, with the specific therapy and dosage determined according to the IRS Group classification system. This study was conducted by collecting secondary data of RMS patients from the medical records consecutively who had been diagnosed and received radiotherapy. The data resources were from Radiotherapy Department and Anatomical Pathology Department of RSUP Dr. Hasan Sadikin Bandung and RSUD Al-Ihsan Bandung, between 2017 and 2023. A total of 31 patients were documented. The age of patients ranging from 3 to 66 years old (mean=34.6), with each of age group (children, adult, elderly) consists of 10, 10, and 11 patients respectively. Based on histologic subtype, most cases of RMS recorded are embryonal subtype (n=10) followed by alveolar RMS and pleomorphic RMS with 6 patients each. The extremities were the most common location (n=13) followed by the head and neck region (n=10). After radiotherapy, 20 cases were accounted as radiosensitive and 11 cases were radioresistant. Thirty one patients with rhabdomyosarcoma have received radiotherapy at two referral hospitals in Bandung between 2017-2023. The tumors in pediatric and elderly patients were more sensitive to therapy. Pleomorphic RMS were the most sensitive subtype, and the larger a tumor, the more sensitive it can be.